HOW DO TRANSFORMATIONAL LEADERSHIP, COMMUNICATION AND SUPPLY CHAIN MANAGEMENT AFFECT COMMITMENT TO CHANGE THROUGH READINESS FOR CHANGE? - Wardani, Ratna; Suhariadi, Fendy; Ratmawati, Dwi; Priyono, Sulih; Suhandiah, Sri; Muliatie, Yurilla Endah (International Journal of Supply Chain Management, 2020)
This study aimed to determine the effect of transformational leadership, communication and supply chain information sharing system on a commitment to change and examine the mediating effect of readiness for change. The data were collected through a survey of 320 health workers in the hospitals of East Java who were involved in the implementation plan of the hospital service system and PL-SEM was used to test the hypotheses. The results of statistical analysis showed that transformational leadership and communication had a positive influence on the commitment to change, and the readiness for change significantly mediated the relationship between transformational leadership and commitment to change. However, it did not mediate communication and commitment to change. The study was carried out cross-sectional in government hospital institutions so that the limitations occurred in recognizing the development of the phenomenon under study.